Perlindungan Hukum Pekerja Outsourcing Pasca Putusan Mahkamah Konstitusi No 27/PUU-IX/2011 - Purnomo, Sugeng Hadi; Komariyah, Enny (Mimbar Keadilan, 2014)
Abstract:Â The outsourcing agreement can only be applied to the work related to core business activities or activities that are directly related to the production process, employers are only allowed to hire workers/laborers with employment agreement specified time and/or work agreement for an unspecified time . The work can be outsourced to the service provider company workers/laborers should be a support service or activity that is not directly related to the production process. The definition of auxiliary service activities or activities that are not directly related to the production process are activities outside the core business (core business) of a company, including business cleaning services (cleaning service); business of providing food for the workers/laborers (caterin); business personnel security (security/security forces); business support services in the mining and petroleum, and transportation business for workers/laborers as article No. 17 minister of labor regulation No. 19 year 2012. The purpose of this study was to determine and analyze the protection of workers Outsourcing based on Law of the Republic of Indonesia Number 13 Year 2003 concerning Manpower, also to know the legal protection of workers after the outsourcing decision of the Constitutional Court No. 27/PUU-IX/2011.Keywords: employment agreements, outsourcing, support services